Occlusion-aware collision avoidance trajectory planning with potential collision risk assessment for autonomous vehicle - Qian, Yubin; Deng, Chengzhi; Xu, Jiejie; Qu, Xianguo; Song, Zhenyu (Bulletin of the Polish Academy of Sciences Technical Sciences, 2024)
Motion planning for autonomous vehicles relies heavily on perception and prediction results to find a safe, collision-free local trajectory that adheres to traffic rules. However, vehicle perception is frequently limited by occlusion, and the generation of safe local trajectories with restricted perception poses a significant challenge in the field of motion planning. This paper introduces a collision avoidance trajectory planning algorithm that considers potential collision risks, within a hierarchical framework of sampling and optimization. The primary objective of this work is to generate trajectories that are safer and align better with human driver behavior while considering potential collision risks in occluded regions. Specifically, in occlusion scenarios, the state space is discretized, and a dynamic programming algorithm is used for a sampling-based search to obtain initial trajectories. Additionally, the concept of a driving risk field is introduced to describe potential collision risk elements within the human-vehicle-road environment. By drawing inspiration from graph search algorithms, potential collision risk areas are accurately described, and a cost function is proposed for evaluating potential risks in occluded regions. Drivers typically exhibit conservative and cautious driving behavior when navigating through occluded regions. The proposed algorithm not only prioritizes driving safety but also considers driving efficiency, thereby reducing the vehicle’s conservativeness when passing through occlusions. The research results demonstrate that the ego vehicle can actively avoid blind spots and tends to move away from occluded regions, aligning more closely with human driver behavior.